A review of iron carbonate (FeCO3) formation in the oil and gas industry. (September 2018) - Barker, Richard; Burkle, Daniel; Charpentier, Thibaut; Thompson, Harvey; Neville, Anne
Abstract: This paper reviews the information in the literature relating to FeCO3 formation in the context of oil and gas production. Numerous factors which influence the kinetics, physical properties and protective nature of FeCO3 are considered in addition to a review of semi-empirical models developed to predict precipitation/corrosion layer accumulation rate. The limitations of current models are discussed and the challenges of conducting deposition studies onto steel surfaces in a controlled environment using laboratory based techniques are also reviewed. Finally, more recently employed experimental techniques are considered in their potential to provide a further understanding of FeCO3 and mixed carbonate kinetics.